Self-Care Behaviors among Type Two Diabetes Mellitus Patients attending Diabetes and Endocrine Center in Sulaimani City – Iraq - Shareef, Omar Hussein; Ramzi, Zhian Salah; Abdulla, Raza M (Sulaimani Journal for Pure and Applied Sciences, 2021)
Type Two Diabetes Mellitus is a chronic disease characterized by elevated blood glucose, polyphagia, polydipsia, and poly-urea. It comes with several devastating complications, including macrovascular and microvascular complications. A patient's self-care behaviors can have a significant role in reducing complications and controlling blood glucose. The overall aim of this study is to assess the self-care behaviors among patients with type 2 diabetes. In this descriptive study, data was collected from October 2020 to January 2021, by which 350 patients consented and were recruited in the study. Self-care scores were obtained by a self-care behavior assessment questionnaire, and patients' clinical parameters were assessed by HbA1c% and fasting blood glucose among the participants. SPSS software version 25.0 was used to determine the self-care behaviors among the patients concerning their socio-demographic characteristics, in which p ≤ 0.05 is considered significant and p > 0.05 is not significant. Generally, participants in this study are a poor self-care score which comprises 59.4% of the sample, and 33% have moderate self-care score meanwhile, only 6.1% have the acceptable level of self-care scores. Negative correlations were found between FBG, HbA1%c, and self-care behaviors. Finally, there are highly significant relationships between level of education, duration of diabetes, types of treatment, and self-care scores
Keywords: Type 2 diabetes mellitus; diabetes and self-care behavior; glycaemic control; complications of diabetes mellitus; Self-care management